2021
DOI: 10.3390/nano11082007
|View full text |Cite
|
Sign up to set email alerts
|

Geopolymers vs. Cement Matrix Materials: How Nanofiller Can Help a Sustainability Approach for Smart Construction Applications—A Review

Abstract: In the direction of reducing greenhouse emissions and energy consumption related to the activities of the cement and concrete industry, the increasingly popular concept of eco-sustainability is leading to the development and optimization of new technologies and low impact construction materials. In this respect, geopolymers are spreading more and more in the cementitious materials field, exhibiting technological properties that are highly competitive to conventional Portland concrete mixes. In this paper, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 104 publications
2
13
0
Order By: Relevance
“…Taking the results of the OPC mixtures as reference values, it is possible to note ECO2 reduction rates close to 30% and 40% for Control-AAM and RP100-AAM mixes, respectively. This finding aligns well with the results reported in a previous review work conducted by the authors (Valente et al, 2021), in which it was found that the AAM technology represents a valid eco-sustainable solution to ordinary cement mixes, bringing on carbon emissions reduction rates up to 80%. For both matrices, an increase in the carbon footprint was estimated by replacing the mineral fraction with the tire rubber aggregate.…”
Section: Eco2 Emissions and Cost Analysissupporting
confidence: 92%
“…Taking the results of the OPC mixtures as reference values, it is possible to note ECO2 reduction rates close to 30% and 40% for Control-AAM and RP100-AAM mixes, respectively. This finding aligns well with the results reported in a previous review work conducted by the authors (Valente et al, 2021), in which it was found that the AAM technology represents a valid eco-sustainable solution to ordinary cement mixes, bringing on carbon emissions reduction rates up to 80%. For both matrices, an increase in the carbon footprint was estimated by replacing the mineral fraction with the tire rubber aggregate.…”
Section: Eco2 Emissions and Cost Analysissupporting
confidence: 92%
“…Utilizing resources economically and effectively has become a priority nowadays. Cement, being the primary component of concrete, has been under criticism in recent decades for the amount of CO 2 emitted during its manufacture [1][2][3]. While cement possesses superior mechanical characteristics, it has been unable to meet the standards of durability [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Other supplementary cementitious materials can possess hydraulic activity, meaning that they can chemically react with water, set and harden [11]. FA have also been used with success in the development of alkali-activated binders [12][13][14][15] a topic that as gaining increasing interest for the development of more sustainable building materials [13][14][15] alternatives to those based on OPC [14,15].…”
Section: Introductionmentioning
confidence: 99%